(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Entrepreneurs play a vital role in an economy as agents of economic growth. They create mechanism that connects different sections of society by enhancing the transmission of goods and services from one end to another. Studies on motivational factors confirms the importance of the role of motivational factors in determining the nature and types of enterprises entrepreneurs would choose to take up. The study reveals that internal motivation (p<0.5) has far greater impact on the entrepreneurs than the external factor. Desire to be self employed and attain financial independence are the most important personal motives driving individuals towards entrepreneurship. Encouragement from family and relatives is found to be an important external factor influencing entrepreneurial success.